Friction Stir Welding in Aircraft Structures: Current and Future Prospects - walid shewakh; Ahmed Abu-Oqail; T. S. Mahmoud; Mohamed Abu-Okail (Yanbu Journal of Engineering and Science)
Friction stir welding (FSW) has significant potential to enhance the efficiency of air transportation systems; however, determining and applying its parameters continues to pose challenges. This article review explores current and future challenges, trends, and practices that facilitate the integration of competitive production into new aircraft structure joints. An overview of friction stir welding techniques used for the design and manufacture of aircraft structures are presented, focusing on product optimization through lightweight and high-strength properties. The implementation of various design solutions and advanced manufacturing technologies can enhance metallic fuselage systems' performance without compromising risk and cost. The paper presents examples of successfully addressed challenges and those driving the development of new practices, design solutions, methods, and tools. Ultimately, aircraft structure joints become more integrated when systems engineering approaches are linked with various design solutions and advanced manufacturing technologies (e.g., Vertical Compensation Friction Stir Welding) in a reusable manner, balancing product performance and producibility. Nevertheless, the field remains in active development, posing challenges for research, development, and practice.